2010
DOI: 10.1074/jbc.m109.068759
|View full text |Cite
|
Sign up to set email alerts
|

Physical Interaction of Jab1 with Human Serotonin 6 G-protein-coupled Receptor and Their Possible Roles in Cell Survival

Abstract: The 5-HT 6 receptor (5-HT 6 R) is one of the most recently cloned serotonin receptors, and it plays important roles in Alzheimer disease, depression, and learning and memory disorders. However, unlike the other serotonin receptors, the cellular mechanisms of 5-HT 6 R are poorly elucidated relative to its significance in human brain diseases. Here, using a yeast two-hybrid assay, we found that the human 5-HT 6 R interacts with Jun activation domain-binding protein-1 (Jab1). We also confirmed a physical interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
61
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 48 publications
3
61
0
Order By: Relevance
“…In addition, the C-terminus and iL3 of 5-HT 6 R selectively interact with the N-terminus and C-terminus of Jab1, respectively. Interestingly, hypoxia increases the expression level of 5-HT 6 R and Jab1, indicating that 5-HT 6 R and the Jab1 complex and its downstream signaling pathway protect the cells against hypoxia (Yun et al, 2010). A recent study has further shown that direct recruitment of CDK5 and p35 (also known as CDK5R1) to the C-terminus of 5-HT 6 R leads to the phosphorylation of this region and promotes neurite outgrowth by activating Cdc42 (Duhr et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the C-terminus and iL3 of 5-HT 6 R selectively interact with the N-terminus and C-terminus of Jab1, respectively. Interestingly, hypoxia increases the expression level of 5-HT 6 R and Jab1, indicating that 5-HT 6 R and the Jab1 complex and its downstream signaling pathway protect the cells against hypoxia (Yun et al, 2010). A recent study has further shown that direct recruitment of CDK5 and p35 (also known as CDK5R1) to the C-terminus of 5-HT 6 R leads to the phosphorylation of this region and promotes neurite outgrowth by activating Cdc42 (Duhr et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Besides Gas, 5-HT 6 R is known to interact with various proteins such as Fyn tyrosine kinase (Yun et al, 2007), Jun activation domain-binding protein-1 (Jab1, also known as COPS5) (Yun et al, 2010), mammalian target of rapamycin (mTOR) (Meffre et al, 2012), microtubule-associated protein 1B light chain (MAP1B-LC) (Kim et al, 2014) and cyclin-dependent kinase 5 (Cdk5) (Duhr et al, 2014). The C-terminus of 5-HT 6 R interacts with the Fyn and activation of 5-HT 6 R stimulates (B-D) HEK293T cells were co-transfected with HA-5-HT6R or HA-b2AR and EGFP-C1 or EGFP-RGSPX.…”
Section: Discussionmentioning
confidence: 99%
“…Although a substantial amount of COPS5 is expressed in the neurons and the brain, the role of COPS5 in the brain is completely unknown. Although most studies on COPS5 reported so far were on non-neuronal cells, a recent study found physical interaction between human serotonin receptor 6 (5-HT 6 R), a G protein-coupled receptor, and COPS5 (33). In this study, siRNA-mediated down-regulation of COPS5 decreased the activity of 5-HT 6 R by reducing its protein expression, suggesting that COPS5 is necessary to maintain the activity and expression of endogenous 5-HT 6 R. In another recent study, COPS5 was detected within the huntingtin aggregates (34).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its coupling to G proteins, the 5-HT 6 receptor interacts with the Src family tyrosine kinase Fyn (9), the Jun activation domain-binding protein 1 (10), and the microtubule-associated protein Map1b (11). The 5-HT 6 receptor also recruits the mammalian Target of Rapamycin (mTOR) Complex 1, and receptor-operated activation of mTOR signaling in prefrontal cortex (PFC) mediates its deleterious influence on cognition (12).…”
mentioning
confidence: 99%